2001
DOI: 10.1016/s0006-3495(01)75870-5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Subdiffusion in Fluorescence Photobleaching Recovery: A Monte Carlo Study

Abstract: Anomalous subdiffusion is hindered diffusion in which the mean-square displacement of a diffusing particle is proportional to some power of time less than one. Anomalous subdiffusion has been observed for a variety of lipids and proteins in the plasma membranes of a variety of cells. Fluorescence photobleaching recovery experiments with anomalous subdiffusion are simulated to see how to analyze the data. It is useful to fit the recovery curve with both the usual recovery equation and the anomalous one, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
260
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(266 citation statements)
references
References 60 publications
5
260
1
Order By: Relevance
“…However, when more detailed analyses are carried out, it has been found in many cases that the entire population of molecules is not moving at this reduced rate, as one would expect for movement through a viscous solution, but instead, multiple populations of molecules with different mobilities are present (e.g., Politz et al, 1998;Wachsmuth et al, 2000;Platani et al, 2002;Pederson, 2002). This is consistent with anomalous subdiffusion, where mobility is constrained either by transient binding to and/or collisions with nuclear entities or by corralling within confinement zones, both of which phenomena impede free diffusion and give rise to multiple subpopulations of molecules moving with different mobilities (Feder et al, 1996;Saxton, 2001). …”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, when more detailed analyses are carried out, it has been found in many cases that the entire population of molecules is not moving at this reduced rate, as one would expect for movement through a viscous solution, but instead, multiple populations of molecules with different mobilities are present (e.g., Politz et al, 1998;Wachsmuth et al, 2000;Platani et al, 2002;Pederson, 2002). This is consistent with anomalous subdiffusion, where mobility is constrained either by transient binding to and/or collisions with nuclear entities or by corralling within confinement zones, both of which phenomena impede free diffusion and give rise to multiple subpopulations of molecules moving with different mobilities (Feder et al, 1996;Saxton, 2001). …”
Section: Discussionmentioning
confidence: 69%
“…When the log ( 2 /dt) is plotted vs. log dt, the degree of anomalous diffusion can be determined, and information about the obstacle concentration is also obtainable in some cases (Saxton, 1994(Saxton, , 2001Platani et al, 2002). We found that 60S subunit diffusion was indeed anomalous in the nucleoplasm; the log-log plots were linear with a very steep slope ( Figure 6B), instead of the zero slope that would be seen with unconstrained diffusion.…”
Section: Molecular Biology Of the Cell 4808mentioning
confidence: 82%
See 1 more Smart Citation
“…Special attention has been paid to slow subdiffusive transport for which meansquared displacement is sublinear x 2 (t) ∼ t μ , where μ is the anomalous exponent μ < 1. Subdiffusion is experimentally observed for proteins and lipids on cell membranes [5], RNA molecules in the cells [6], transport in spiny dendrites [7], etc. The major feature of this process is the absence of the characteristic microscopic time scale.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of information about motion of molecules in living cells has been obtained from intracellular measurements using different experimental techniques [7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and from simulations [10,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Experimental data are usually obtained by fluorescence recovery after photobleaching (FRAP) [12-14, 16, 18, 20, 28, 30], fluorescence correlation spectroscopy (FCS) [11-23, 26-27, 29] and single particle tracking (SPT) [15,19,[24][25] techniques.…”
Section: Introductionmentioning
confidence: 99%